HIV/AIDS - Harda Afif Franda Sinaga (Calory Journal Medical Laboratory Journal, 2025)
Human Immunodeficiency Virus (HIV) is a retrovirus that targets the human immune system, particularly cells with CD4 receptors such as T lymphocytes, monocytes, and macrophages. This virus causes progressive damage to the immune system and, if left untreated, can develop into Acquired Immunodeficiency Syndrome (AIDS). HIV is transmitted through sexual contact, blood transfusions, shared needles, and from mother to child during pregnancy, childbirth, or breastfeeding. HIV has become a global pandemic, with over 39 million people living with the virus in 2022. In Indonesia, the HIV epidemic is diverse, with high-risk groups including injection drug users, men who have sex with men, sex workers, and transgender individuals. The pathogenesis of HIV involves infection of immune cells, integration of viral DNA into the host genome, and production of new virions, leading to a gradual decline in immune function. HIV diagnosis is conducted through serological and virological testing, while antiretroviral therapy (ART) is the standard treatment to suppress viral replication, preserve immune function, and improve patients' quality of life and life expectancy. Early detection and proper management of HIV are crucial to preventing progression to AIDS and reducing transmission within the population.